Systemic Risk, Dollarization, and Interest Rates in Emerging Markets - Bacha, Edmar L.; Holland, Márcio; Gonçalves, Fernando M. (World Bank, 2012)
This study investigates the impact of systemic risks and financial dollarization on real interest rates in emerging economies. Higher systemic risks induce both higher real interest rates and increased dollarization. Using appropriate instruments for the dollarization ratio, the study overcomes the simultaneous equation problem and correctly estimates a negative coefficient for the dollarization ratio in the interest rate equation. It confirms the theoretical prediction that a strategy of "dedollarizing" the economy will raise the equilibrium domestic real interest rate if the strategy fails to address fundamental macroeconomic risks. Even so, it also finds that this effect is small, after controlling for the risks of dilution and default. The results bring to light the systemic-risk reasons for high interest rates in emerging economies—and contribute to evaluating the difficulties of dedollarization policies.